2004
DOI: 10.1023/b:chud.0000039321.56041.cd
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Translation and Reliability Testing of the Child Depression Inventory

Abstract: The goal of this study was to test the internal reliability of a Spanish translation of the CDI, (i.e., CDI-LA), a potentially useful screening instrument for Hispanic youngsters in their native language at a primary-care level. Self-reported symptoms of depression were assessed with the CDI-LA in a school sample of 205 Hispanic students. Girls and boys ranging from 8 to 15 years (mean age 11.5 +/- 1.9 years) were tested on a designated day. The CDI-LA mean score was 9.7 +/- 7.2. Eleven percent of the subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 29 publications
5
42
0
3
Order By: Relevance
“…Depression was defined as the CDI-S total score equal or higher than 7. 19 The internal consistency coefficient for the CDI-S in this sample was Cronbach's a = 0.75.…”
Section: Study Design and Participantsmentioning
confidence: 70%
“…Depression was defined as the CDI-S total score equal or higher than 7. 19 The internal consistency coefficient for the CDI-S in this sample was Cronbach's a = 0.75.…”
Section: Study Design and Participantsmentioning
confidence: 70%
“…Depressive symptoms were screened by the short version of the Child Depression Inventory [CDI,17]. It has been shown to be a reliable and useful method for examining children and adolescents [1,7,19,25]. We excluded those children who scored above sevenpoints, reported as a clinical cut-off for depression in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…it covers depressive symptoms according to the DSM IV [3] and the items are scored quantitatively reflecting growing severity of symptoms). Previous research has shown that the CDI is adequately reliable and valid with respect to depressive symptoms [9,14,25,31,33,44,47,49,56]. In general populations the CDI mean score and standard deviation is around 9 ± 7, and its internal consistency evaluated with Cronbach's alpha ranges from 0.71 to 0.87 [8,32,42].…”
Section: Introductionmentioning
confidence: 99%